2020
DOI: 10.1111/os.12730
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Vertebroplasty with Side‐Opening Cannula or Front‐Opening Cannula in the Treatment of Kummell Disease?

Abstract: Objective To explore the effect of bone cement distribution, cement leakage, and clinical outcomes with side‐opening cannula for bone cement injection in percutaneous vertebroplasty (PVP) in treatment of Kummell disease. Methods A prospective study of patients with Kummell disease undergoing PVP was conducted from April 2012 to September 2017. In total, 43 patients (11 males, 32 females) with Kummell disease who received bilateral PVP were included in the study. The patients were divided into front‐opening can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…[1][2][3] The lesions are usually located in the thoracolumbar region and affect a single-level vertebra in the majority of cases. 4,5 KD has rarely been reported in previous studies and can easily be misdiagnosed as a pathological fracture. With advanced imaging technology and additional medical knowledge, more KD cases are being detected, and the prevalence of KD ranges from 7% to 37% among people with osteoporotic vertebral fractures.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…[1][2][3] The lesions are usually located in the thoracolumbar region and affect a single-level vertebra in the majority of cases. 4,5 KD has rarely been reported in previous studies and can easily be misdiagnosed as a pathological fracture. With advanced imaging technology and additional medical knowledge, more KD cases are being detected, and the prevalence of KD ranges from 7% to 37% among people with osteoporotic vertebral fractures.…”
Section: Introductionmentioning
confidence: 89%
“…17 , 18 The evidence available has confirmed that PVP is a safe and effective surgical procedure for KD. 1 , 5 , 19 PKP is more conducive to restoring vertebral height and correcting kyphosis and is considered a better choice for patients with significant vertebral height loss (HL) and old fractures with pseudarthrosis. 20 - 22 However, because bone cement is injected into the compressed vertebral body under a large pressure, PKP and PVP may cause associated complications, with bone cement leakage being the most common complication.…”
Section: Introductionmentioning
confidence: 99%
“…More aggressive treatment options comprise of nerve root blockage, vertebral body augmentation, and open surgery [ 6 ]. In neurologically intact patients with painful vertebral fracture, most authors recommend percutaneous vertebral body augmentation with vertebroplasty or kyphoplasty [ [7] , [8] , [9] ]. In these minimally invasive procedures, the unstable vertebra is reconstructed and filed with orthopedic cement and the patient's pain and disability are eliminated immediately after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…The disease has some characteristic (non-diagnostic) features on imaging that help to differentiate it from post-traumatic kyphosis, infection, osteoporotic fracture, or metastatic involvement [ 4 , 5 ]. Most symptomatic patients show a satisfactory response to conservative or minimally invasive measures such as percutaneous vertebral body cement augmentation, but in those patients with neurological deficit, open surgery may be indicated [ [6] , [7] , [8] , [9] , [10] , [11] ]. Here, we reported a case of a 28 years-old man with KD who presented to us with impending cauda equina syndrome due to L5 involvement which is extremely rare in this disease [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the cavity and pseudojoint, the vertebral body is unstable, as the disease progresses, patients with Kümmell will gradually develop symptoms such as progressive kyphosis, intractable back pain, or neurological deficits, which seriously affect the quality of life. For Kümmell's disease, non-surgical treatment is usually less effective and carries a risk of pneumonia, bedsores, venous thrombosis of the lower limbs, or delayed neurological deficits 10,11 . At present, surgical treatment of Kümmell's disease is recommended.…”
Section: Introductionmentioning
confidence: 99%